Understanding Mediterranean Pasture Dynamics: General Tree Cover vs. Specific Effects of Individual Trees - De Miguel, José Manuel; Acosta-Gallo, Belén; Gómez-Sal, Antonio (Rangeland Ecology & Management, 2013)
The study investigated the effect of general and homogeneous tree cover on grassland composition on an extensive Mediterranean rangeland with sparse oak trees in central Spain. We analyzed this effect together with other significant factors identified in this type of rangeland: topography and plowing. Data were collected in the 1984 growing season and they form part of a historical database on the characteristics of vegetation and livestock behavior; these data refer to grasslands below and away from the tree crowns of 91 individual trees, located in different topographical positions and in areas that were last plowed at different times.We used multivariate analyses to identify the main compositional trends of variation in pasture communities. The results indicate that the herbaceous community below tree crowns was more similar to that of the lowland areas than to the nearby areas away from the tree. This result supports the idea of tree cover in semiarid rangelands as a factor attenuating the effects on pastures of environmental conditions typical of high and intermediate topographical positions—generally presenting low soil moisture and fertility. Coupled with this, we also found effects of some individual trees related with the way livestock uses them as shelter and resting places. Our results indicate that the role played by dispersed trees in the management of this type of rangeland should be analyzed at two complementary spatial scales: the overall effect of tree cover as a factor acting at landscape scale and the specific effect of some individual trees acting at a more detailed scale.
Keywords: free-ranging livestock; pasture management; Quercus ilex; scattered trees; Silvopastoral systems; topography effect

The importance of grazing regime in the provision of breeding habitat for grassland birds: The case of the endangered little bustard (Tetrax tetrax) - Faria, Nuno; Rabaça, João E.; Morales, Manuel B. (Journal for Nature Conservation, 2012)
In Mediterranean dry grasslands, grazing by domestic animals is an important agricultural activity on dry grasslands. Several bird species occur in these grazed habitats and are now experiencing a near continuous decline. We investigated the impact of livestock grazing on the threatened little bustard (Tetrax tetrax L.). The study was conducted at the NATURA 2000 Site/Important Bird Area of Cabrela, Portugal. Our main goals were to investigate responses of little bustard territorial males and breeding females to different livestock management practices, namely pasture types, stocking rates and sward structure. Bird distribution was surveyed using car and foot surveys. Data on grazing was supplied by land managers every 10 days from February to June through ﬁeld interviews. Generalised additive models and model averaging were used to compute predictive models. Results indicate that higher probabilities of occurrence were found in long-term pastures and under light-moderate grazing conditions (stocking rates around 0.4 LU/ha). Conversely, lower probabilities of occurrence were found in ungrazed or heavy grazed ﬁelds. Males occurred mostly in large ﬁelds, but this variable seemed to be less important for females. On the other hand, green plant cover and the vegetation height were good predictors for the occurrence of females but not for males. Females used mostly pastures with vegetation height around 20–25 cm. Our results suggest that grazing management plans that aim to conserve little bustard populations should consider (1) the maintenance of the larger long-term pastures and (2) the use of light-moderate stocking rates (0.2–0.6 LU/ha).
Keywords: Green plants; livestock; pasture management; Stocking rates; Tetrax tetrax; vegetation structure